Phương pháp hướng phân giác giải bài toán tối ưu hóa không ràng buộc tổng quát - Manh, Nguyen Van; Tri, Bui Minh; Loan, Nguyen Thuc (Journal of Computer Science and Cybernetics, 2018)
In this paper the general unconstrained optimization problem ts considered. Here are new method, called the method of “bisector direction”, is proposed for solving this problem. Our algorithm is based on  the convergence theorems and it has a high rate of  convergence. Some example are given also.